Recurrence of Colonic Diverticulitis: Identifying Predictive CT Findings—Retrospective Cohort Study - Dickerson, Elliot C.; Chong, Suzanne T.; Ellis, James H.; Watcharotone, Kuanwong; Nan, Bin; Davenport, Matthew S.; Al-Hawary, Mahmoud; Mazza, Michael B.; Rizk, Rafat; Morris, Arden M.; Cohan, Richard H. (Radiology, 2017)
Purpose To identify computed tomographic (CT) findings that are predictive of recurrence of colonic diverticulitis. Materials and Methods Institutional review board approval was obtained for this HIPAA-compliant, retrospective cohort study. Six abdominal fellowship-trained radiologists reviewed the CT studies of 440 consecutive subjects diagnosed with acute colonic diverticulitis between January 2004 and May 2008 to determine the involved segments, maximum wall thickness in the inflamed segment, severity of diverticulosis, presence of complications (abscess, fistula, stricture, or perforation), and severity of the inflammation. Electronic medical records were reviewed for a 5-year period after the patients' first CT study to determine clinical outcomes. Predictors of diverticulitis recurrence were assessed with univariate and multiple Cox proportional hazard regression models. Results Colonic diverticulitis most commonly involved the rectosigmoid (70%, 309 of 440) and descending (30%, 133 of 440) colon segments. Complicated diverticulitis was present in 22% (98 of 440) of patients. On the basis of the results of univariate analysis, significant predictors of diverticulitis recurrence were determined to be maximum colonic wall thickness in the inflamed segment (hazard ratio [HR], 1.07 per every millimeter of increase in wall thickness; P < .001), presence of a complication (HR, 1.75; P = .002), and subjective severity of inflammation (HR, 1.36 for every increase in severity category; P value for linear trend = .003). The difference in maximum wall thickness in the inflamed segment (HR, 1.05 per millimeter; P = .016) and subjective inflammation severity (HR, 1.29 per category; P = .018)remained statistically significant in a Cox multiple regression model. Conclusion Maximum colonic wall thickness and subjective severity of acute diverticulitis allow prediction of recurrent diverticulitis and may be useful for stratifying patients according to the need for elective partial colectomy. RSNA, 2017 Online supplemental material is available for this article.